E-Learning Development Based on Schoology for Subject of Information and Communication Technology Grade VII using Flipped-Learning Approach - Warsito, Mikha Bimantara; Haryono, Haryono; Wibawanto, Hari (Universitas Negeri Semarang, 2019)
Information technology began to be used in solving problems that exist in the education field, especially in the learning process. The existence of information technology is increasingly developing the conventional learning process that has various weaknesses. One of the information technology products used in the learning process is Electronic Learning: E-Learning. This study aims to develop E-Learning facilities at Pelita Harapan Bangsa Tegal Middle School. The use of the Flipped Learning approach, or it can also be called an inverted class now became popular when E-Learning is applied in teaching development and learning activities. This research includes the type of development research concerning the opinion of Borg and Gall. Products developed based on initial research is Schoology learning management system (NGOs) using the Flipped learning approach for class VII students Mail Merge eye containing materials on ICT subjects. The subjects in this trial were the subject matter of research development experts items, namely materials experts, learning media experts, and teachers, as well as subjects of class VII of Pelita Harapan Bangsa in Tegal City Middle School as potential users of the product. The technique of the data collection was done by questionnaire. This questionnaire was used to assess products that were developed in terms of product feasibility. Data were descriptively analyzed quantitatively and qualitatively. Based on the tests that had been carried out, it can be assumed that the Schoology-assisted Flipped Learning approach is Appropriate to use and can increase student activity and interest in learning. The use of flipped learning helped by Schoology can be beneficial to the development of education as a whole such as long-distance learning and can be more efficient and effective in terms of collection and delivery of tasks.